Tax-based own resources to finance the EU budget: Potential revenues, summary evaluation from a sustainability perspective, and implementation aspects - Margit Schratzenstaller; Alexander Krenek (Austrian Institute of Economic Research (WIFO), 2019)
The existing EU system of own resources financing EU expenditures does not make any positive contribution to the various EU strategies and policies implemented to cope with the manifold long-term challenges confronting the EU. It is against this background that the European Commission as well as the High Level Group on Own Resources, but also the European Parliament have (repeatedly) called for the introduction of tax-based own resources to partially substitute national contributions to the EU budget. Our specific contribution to this debate consists in the exploration of sustainability-oriented options for tax-based own resources which are able to support sustainable growth and development in the EU. Based on a concept of sustainability-oriented taxation in the context of own resources for the EU, we develop sustainability-oriented evaluation criteria to assess the suitability of specific candidates for tax-based own resources. We then present various options for tax-based own resources and estimations of their revenue potential. Moreover, a summary evaluation of these options based on our evaluation criteria is undertaken. Finally, we address implementation aspects. In particular, we briefly present and discuss potential models to implement tax-based own resources in the EU within the existing legal framework.
Keywords: F55; H23; H87; Q58; 330; EU system of own resources; tax-based own resources; EU budget; sustainability-oriented taxation